Ucraïna, mon amour de Carles Torner o la (auto)traducció com un acte d'amor. - Ugalde, Esther Gimeno (Zeitschrift für Katalanistik, 2025)
This article aims to analyze Ucraïna, mon amour (Torner, 2023), a novel featuring the Catalan translator of I. B. Singer as a paradigmatic example of the so-called «transfiction». Singer's presence, also portrayed as a character within the fiction, allows for a profound reflection on the intimate link between writing and translation, concurrently connecting the various 20th-century exiles with the current war in Ukraine. The analysis focuses on the multiple meanings and metaphors associated with translation, such as cultural bridge, journey, exile, survival, resistance, and, above all, love. Through the literary motif of translation, the intertextual dialogues with the works of the writer in Yiddish and other authors, including Carles Torner, will be explored. The article also examines different translation scenes that unfold throughout the novel.